Produksi Asam Laktat dari Fermentasi Limbah Cair Olahan Kelapa dengan Variasi Konsentrasi Inokulum Lactobacillus acidophilus - Ratna Ratna; Ulfa Triovanta; Darwin Darwin (Fakultas Teknik, 2020)
The aim of this research is to study the fermentation technique of coconut processed liquid waste by varying the inoculum concentration of Lactobacillus acidophilus bacteria for lactic acid production. This research was carried out in several steps, namely the first step was the inoculum cultivation process of Lactobacillus acidophilus bacteria, the second step was the fermentation process of coconut water with variations in the concentration of Lactobacillus acidophilus bacteria inoculum, namely 5%, 10% and 20%. Analysis of lactic acid products, pH, glucose, Total Dissolved Solid (TDS), Total Suspended Solid (TSS) and Volatile Suspended Solid (VSS). The variation in the concentration of Lactobacillus acidophilus bacteria inoculum 20% is the most optimum to produce total lactic acid for batch and continuous systems. The results of the correlation analysis for inoculum variations of 5%, 10% and 20% had a strong relationship with lactic acid production, decreased pH and decreased glucose levels. The greater the inoculum concentration, the greater the decrease in the TDS, TSS and VSS content.